Evaluation of the transmission of Bovine Viral Diarrhea Virus by transplacental route in pregnant females experimentally inoculated - Zambotti, Beatriz Belloni [UNESP]; Claro Martines, Mariela Aparecida [UNESP]; Mechler Dreibi, Marina Lopes [UNESP]; Storino, Gabriel Yuri [UNESP]; Ferreira, Marcela Manduca [UNESP]; De Oliveira, Luis Guilherme [UNESP] (Univ Federal Ceara, Centro Ciencias Agrarias, 2020)
Pigs, in natural conditions, can become infected with the bovine viral diarrhea virus (BVDV), a pestivirus of ruminants that leads to reproductive and economic losses. The final third of pregnancy is a critical period for gilts due to stress and the consequent immunological drop. Thus, the objective was to promote the experimental inoculation of gilts with BVDV-2 and to evaluate the capacity of virus transmission to fetuses in a critical period of stress and immunosuppression. Six pregnant gilts were inoculated between the 105th and 110th day of gestation, the piglets born underwent blood collection (to obtain whole blood and serum) and an umbilical cord fragment at birth prior to colostrum ingestion, and had blood collected weekly up to 21 days of age. Samples from all placentas were also collected. Two gilts composed the control group, and their piglets underwent the same procedures. The blood, umbilical cord and placental fragments samples were submitted to RT-PCR evaluations, while the serum was evaluated by the virus neutralization test. There was no evidence of viral transplacental transmission to fetuses in the evaluated period.
Keywords: BVDV; experimental inoculation; piglets; reproductive losses